A conceptual framework for the application of Islamic private equity in international shipping - Abdullah, Adam; Hassan, Rusni; Kassim, Salina (International Islamic University Malaysia, 2016)
This paper aims to assess the application of Islamic private equity in order to develop Islamic finance and investment in international shipping. Shipping is a strong growth industry with about 85% of the global trade carried by the international shipping industry. The problem is that shipping is a highly capital intensive industry, and currently 75% of ship lending has been conducted by European banks and financed on a conventional basis. The post-financial crisis, shipowners, ship lenders and shipyards have all been exposed to the impact of over-levered balance sheets and debt finance. Our conceptual framework discusses how Islamic finance and investment institutions can participate at the retail and institutional levels involving private equity. Our study suggests that Islamic private equity should appeal to retail and institutional investors to promote and develop international shipping from Malaysia, in line with government policies on shipping and Islamic finance.